Informasi Geografis Untuk Mengetahui Jalur Rawan Kecelakaan Di Kabupaten Sidoarjo Menggunakan Gps Berbasis Android - Nurul amiroh; Ade Eviyanti, S. Kom (International Journal of Human Computing Studies, 2020)
Sidoarjo is a densely populated city, with a high population level so that the movement of mobilization of transportation facilities and infrastructure is also increasing. From that impact arises congestion problems and a relatively high level of traffic accidents from year to year. Traffic accidents according to RI Law Article 1 No. 22 of 2009 Article 1 is an incident on an unexpected and unintentional highway involving a vehicle with or without other road users resulting in human casualties and / or property losses. In the occurrence of an accident, it always contains elements of accidental and uninjured and will cause feelings of surprise, surprise and trauma for people who have experienced the accident. If an accident occurs intentionally and has been planned in advance, then this is not a traffic accident, but is classified as a criminal act of either persecution or premeditated murder. Based on the results of trials conducted on three Android devices, this application runs well on all types of Android devices with different OS versions. In terms of appearance, this application uses a layout with listview, so that the display will adjust to the resolution of the Android device. While in terms of stability, it is a bit heavy on some android devices due to the specifications.